Photodynamic Therapy as an adjunct in the Treatment of Medication-Related Osteonecrosis of the Jaw: A Case Report - Almeida, Marcelo Vieira da Costa; Moura, Antonio C.; Santos, Lúcia; Gominho, Luciana; Cavalcanti, Ully Dias Nascimento Távora; Romeiro, Kaline (Journal of Lasers in Medical Sciences, 2021)
Introduction: Medication-related osteonecrosis of the jaws (MRONJ) corresponds to an adverse effect of the use of drugs such as Bisphosphonates and Denusomab. The management of MRONJ tends to be conservative, through the guidance of oral hygiene, antibiotic therapy and mouthwashes. However, the use of antimicrobial photodynamic therapy (aPDT) has shown promise in the treatment of these injuries. The purpose of this article is to report a case of MRONJ treatment associated with aPDT. Case report: A 75-year-old patient, with a history of breast cancer and use of intravenous Zoledronic Acid, presented with bilateral MRONJ lesions in tuberosity on the right and left sides. Treatment was conservatively instituted with the use of aPDT as an adjuvant. After 12 aPDT sessions, complete regression of the lesion was observed. However, after two weeks, the presence of a new lesion was noted, this time in the anterior region of the maxilla. The same protocol previously established was followed and after two aPDT sessions, the patient returned with complete lesion regression. Conclusion: The use of aPDT may represent an important adjuvant within a set of clinical protocols in the treatment of MRONJ. DOI:10.34172/jlms.2021.12